Understanding the Dreyfus model of skill acquisition to improve ultrasound training for obstetrics and gynaecology trainees. (May 2014) - Field, Alexander
There have been significant problems in ultrasound training since the introduction of the new postgraduate curriculum for obstetrics and gynaecology. It is therefore important to understand how the skill of ultrasound is acquired in order to be able to improve the training program. Here, the potential application of the Dreyfus model of skill acquisition has been analysed to map the progression from novice to master and the progressions between each stage analysed. Although the Dreyfus model is not a perfect match for ultrasound scanning, it provides us with a theoretical framework on which to underpin educational practice in this field.